Iron bioavailability - Winichagoon, Pattanee (Journal of Nutrition Association of Thailand (Online), 2017)
Animal food sources contain heme and non-heme iron in variable proportions. Red meat, liver and blood have higher heme iron than white flesh foods (poultry, fish). Iron in milk and egg, plant sources (cereal grains, pulses and legumes), and iron fortificants are in the non-heme forms. Heme iron can be readily absorbed for utilization, whereas bioavailability of non-heme iron is affected by other food components that are present in the same meal. These food components may enhance (e.g., ascorbic acid), or inhibit iron absorption. The main iron absorption inhibitors in foods are phytate and polyphenols, which are also present in plant foods. In order to obtain adequate iron intakes, content and form of iron in foods,food portions eaten and co-present of iron absorption enhancers and inhibitors must be considered. In addition, iron status of individuals, physiological demands (e.g., growth, female reproductive age, pregnancy) also determine iron bioavailability from foods. Promoting good iron nutrition needs to consider diversity of foods or selecting bioavailable iron in food fortification. Absorption of iron from supplemented iron is reduced if taken together with meals, although side effects could be less. Taking iron supplement between meals is more desirable. Hemoglobinopathy, a hereditary abnormality in hemoglobin production, is common in Southeast Asia and other parts of the world. The majority of people having hemoglobinopathy are carriers or trait, and may have iron deficiency if the diets contain inadequate iron. The same strategies for ensuring adequate iron nutrition for people who have normal hemoglobin type can be promoted.